PECTIN ACTIVITY IN RESPECT OF CHOLERIC VIBRION BIOFILMS - N. A. Selyanskaya; L. A. Yegiazaryan; S. N. Golovin; E. G. Potiyevskiy; L. M. Verkina; N. G. Zheleznyak (Антибиотики и Химиотерапия)
The growth of antibiotic resistance of cholera vibrios causes interest in a group of substances of plant origin possessing antimicrobial activity. The purpose of this work was to study the antibacterial properties of pectin in relation to Vibrio cholerae and biofilms formed by it. A 1.0-5.0% solution of pectin caused death of cholera vibrios of various serogroups, both antibiotic-sensitive and possessing multiple antibiotic resistance, when exposed for a total of 1 hour. Biofilms were slightly more resistant to 1.0% pectin and showed high sensitivity to 2.0-5.0% solution of pectin, which also prevented the formation of biofilms. With the help of transmission electron microscopy it was shown that as a result of the action of 5.0% pectin solution within 1 hour a pronounced destruction of the matrix with complete destruction of cholera vibrio cells was observed. The study shows the promise of using pectins in the treatment and prevention of diseases caused by V.cholerae.